DEVELOPMENT OF THE SECURITIES MARKET IN UZBEKISTAN: IMPROVEMENT OF THE REGULATORY AND LEGAL FRAMEWORK AND DIGITALIZATION TRENDS - F. Muxamedov; A. Ibodullayev (American Journals Publishing, 2025)
This article analyzes the development of the securities market in the Republic of Uzbekistan from 2019 to 2024, the improvement of the regulatory and legal framework, and the process of implementing digital technologies. The 2023 report of the "Tashkent" Republic Stock Exchange, regulatory documents on internal control from 2019 and 2021, and the procedure for remote digital identification of clients in 2024 were used to study the transparency, security, and alignment of the market with international standards (FATF, KYC, AML/CFT). The results show that the legal infrastructure of the market has been strengthened, digitalization has improved convenience for investors, but liquidity and technological infrastructure constraints remain. Based on international experience (India, European Union), recommendations for future development were provided.
Keywords: Securities market, internal control, digital identification, stock exchange, regulatory and legal framework, AML/CFT, KYC, FATF, Uzbekistan, digitalization.